Spatial analysis of Shiraz urban areas in terms of social justice with an emphasis on public services - Mohamad hadi Setavand; Fazel Hajizadeh; Hosin Yaghfoori (تحقیقات کاربردی علوم جغرافیایی)
Urban Public Service structuring the form and nature of the physical, social and spatial city; Therefore injustice in how to distribute it, the structure, on nature of the city and class segregation affects urban areas and Urban management is faced with serious challenges. In the same vein, the main purpose of this study, Spatial analysis of enjoyment levels ten main areas of the Shiraz city of Urban service. The research method is descriptive-analytical and its type is practical. In collecting data library method and field has been used. The statistical population of ten main areas of the Shiraz city that according to the 10 overall index and 49 components crucial public services Assessed. For analysis and grading the urban districts from the view point of enjoing public services, some models including Fuzzy TOPSIS, VIKOR and WASPAS have been used and for reaching to a unified result in data analysis of different models, the blended average of ranks has been used. The results of this method showed that Areas 1, 2 and 4 have in the first rank, areas 3, 6 and 7 in the category semi, Districts 8 and 10 low Enjoyment and Zones 5 and 9 enjoyment been lacking in class. The findings of this study show that the distribution of public services in areas of City Shiraz with Spatial justice approach does not match .At the end of this article, strategies according to research findings been proposed.